2015
DOI: 10.1371/journal.pone.0136410
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Poor Mental Health in Relation to Economic Status: The Case of Cambodia 35 Years Later

Abstract: BackgroundCambodia is one of the poorest countries in south-east Asia and is still emerging from the events of the Khmer Rouge reign. It has been suggested that the atrocities experienced by the Cambodian population can explain why Cambodia continues to lag behind its neighbours in economic outcomes. The purpose of this study is to investigate whether there is an association between exposure to past trauma and/or current poor mental health and current economic status in Cambodia.MethodA newly conducted survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The findings from this study are consistent with previous findings from adult samples that have indicated differences in PTSD symptoms and mental health outcomes depending on the region of Cambodia (Cantor Graae et al., ; Jarl et al., ). However, these previous studies were conducted with samples from only two of Cambodia's unique geographic regions and did not account for individuals nested within those regions.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The findings from this study are consistent with previous findings from adult samples that have indicated differences in PTSD symptoms and mental health outcomes depending on the region of Cambodia (Cantor Graae et al., ; Jarl et al., ). However, these previous studies were conducted with samples from only two of Cambodia's unique geographic regions and did not account for individuals nested within those regions.…”
Section: Discussionsupporting
confidence: 92%
“…Testimonial therapy has been previously used in Cambodia and has served as an opportunity for communal and individual healing (Agger, Igreja, Kiehle, & Polatin, 2012). As the model demonstrated that current stressors at individual and community levels were more salient than previous war traumas in impacting PTSD symptoms, such interventions need to be combined with a focus on alleviating poverty and providing more accessible mental and physical health care (Jarl et al, 2015;Seponski, Lewis, & Megginson, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations